Performance of greengram (vigna radiata( L.) wilczek) cultivars under different tillage methods - Abid, V (Department of Agronomy, College of Horticulture, 2018)
An experiment entitled “Performance of greengram (Vigna radiata (L.) Wilczek) cultivars under different tillage methods” was undertaken to study the response of selected greengram cultivars under different tillage methods and to identify the most economical combination of cultivar and tillage. The experiment was conducted during the period from December 2017 to March 2018 at Agronomy Farm, College of Horticulture, Vellanikkara. Split plot design was adopted with three replications. The main plot treatments were four tillage methods viz., M1 - minimum tillage (primary tillage only), M2 - minimum tillage followed by pre-emergence application of pendimethalin @ 1 kg ha-1, M3 - minimum tillage followed by post-emergence application of imazethapyr + imazamox @ 80 g ha-1 at 20 DAS and M4 - conventional tillage (Primary and secondary tillage) followed by two hand weedings at 15 and 30 DAS. Sub plot treatments were four cultivars; V1 –CO 6, V2 –CO 7, V3 –CO 8 and V4 -VBN (Gg)2. The growth attributes of greengram (plant height, number of branches and leaf area) at flowering and at harvest stages were influenced by tillage methods. Higher values were observed in minimum tillage followed by application of herbicide imazethapyr + imazamox @ 80 g ha-1 at 20 DAS and the lowest in minimum tillage. Among the cultivars, CO 8 and VBN (Gg)2 had recorded higher growth parameters. The physiological parameters, CGR, LAI, LAD and number of nodules per plant also varied with tillage methods and cultivars. The results revealed that yield parameters as well as yield were influenced by tillage methods and cultivars. Minimum tillage followed by application of imazethapyr + imazamox @ 80 g ha-1 at 20 DAS resulted in higher number of pods and number of seeds per pod and was at par with conventional tillage method. Among the cultivars, higher values of yield components were recorded in CO 8 followed by VBN (Gg)2. Minimum tillage followed by application of imazethapyr + imazamox @ 80 g ha-1 at 20 DAS recorded higher seed yield (748 kg ha-1) which was at par with conventional tillage. This was 102 per cent higher than yield from minimum tillage. The cultivar CO 8 recorded the highest seed yield (736 kg ha-1) and differed significantly from other three cultivars. All cultivars performed better under minimum tillage followed by application of imazethapyr + imazamox @ 80 g ha-1 at 20 DAS and conventional tillage followed by two hand weedings at 15 and 30 DAS. Among the interactions, the cultivar CO 8 in minimum tillage followed by imazethapyr + imazamox @ 80 g ha-1 recorded higher seed yield (942 kg ha-1) and it was at par with conventional tillage. The results revealed that weed density and dry weight varied with tillage methods but not with cultivars. The weed density was lower in conventional tillage method which was at par with minimum tillage followed by herbicide sprays. The soil nutrient status was not influenced by the cultivars. Among the tillage methods, minimum tillage method recorded higher values of available nitrogen, phosphorus and potassium after the experiment. The nutrient uptake was higher in minimum tillage followed by post emergence application of imazethapyr + imazamox @ 80 g ha-1 at 20 DAS. Economic analysis revealed that cultivar CO 8 grown under minimum tillage followed by imazethapyr + imazamox @ 80 g ha-1 at 20 DAS (M3V3) recorded the highest gross returns and benefit - cost ratio. Greengram cultivar CO 8 (V3) grown under minimum tillage method followed by post emergence herbicide spray of imazethapyr + imazamox @ 80 g ha-1 at 20 DAS (M3) can be recommended for summer rice fallows considering the yield and profitability.